Refrigeration systems and applications - Dinçer, İbrahim, 1964- (Wiley, 2010)
Refrigeration Systems and Applications, 2 nd edition offers a comprehensive treatise that addresses real-life technical and operational problems, enabling the reader to gain an understanding of the fundamental principles and the practical applications of refrigeration technology. New and unique analysis techniques (including exergy as a potential tool), models, correlations, procedures and applications are covered, and recent developments in the field are included - many of which are taken from the author's own research activities in this area. The book also includes some discussion of global.
Keywords: Cold storage.; Frozen foods.; Refrigeration and refrigerating machinery.; elektronické knihy; electronic books